Comparative Analysis of Volatile Terpenoids Composition in Rosemary Leaves in Response to Ionizing Radiation. Issue 3 (3rd May 2020) - Chung, Moon-Soo; Lee, Gun Woong; Lee, Seung Sik; Chung, Byung Yeoup; Lee, Sungbeom
Abstract: This study examined differential regulation of volatile terpenoids produced by rosemary ( Rosmarinus officinalis L.) leaves in response to ionizing irradiation. Headspace volatile collection from rosemary leaves by solid-phase microextraction-gas chromatography-mass spectrometry analyses revealed that rosemary leaves biologically synthesized 26 species of volatile terpenoids and their relative ratio were changed after the exposure to γ-irradiation. Relative ratio of oxygenated monoterpenes such as borneol, (-)-verbenone, lemonol, and bornyl acetate (except for 1, 8-cineol, linalool, chrysanthenone, camphor, and (+)-verbenone) and sesquiterpene hydrocarbons (i.e., caryophyllene-type) increased when the rosemary leaves were exposed to γ-ray in a dose-dependent manner. On the contrary, the change of the ratio of oxygenated sesquiterpenes such as caryophyllene oxide was negligible, and that of monoterpene hydrocarbons like α-pinene, camphene, myrcene, and limonene was down-regulated. These results indicate that γ-irradiation can modify chemical structures of volatile terpenes, and can, thus, be applied to reconstitute chemical constituents in aromatic plants.